CHALLENGES AND OPPORTUNITIES OF DIGITAL INTEGRATION IN MARKETING: A BUSINESS PERSPECTIVE IN EMERGING ECONOMY - Valeri Gagauz (Economy and Sociology)
The article presents the findings of a study on the use of digital marketing in entrepreneurship in Moldova. The study employed a case study approach, conducting in-depth interviews with representatives from five companies of varying sizes operating in the B2C segment. The results revealed that all companies prioritize lead generation, underscoring their commitment to attracting new customers. Using customer relationship management (CRM) systems indicate a strategic focus on fostering long-term customer relationships and re-engagement. Some companies emphasize branding, highlighting the significance of a strong brand in cultivating customer trust and loyalty. Seasonal promotions are a popular strategy for all companies to increase sales during certain periods of the year. LTV pricing is a common practice among automobile companies, which helps them maximize profits from each customer. The variety of advertising campaigns through social networks highlights the importance of these platforms in modern marketing. The findings also suggest that despite the availability of online platforms, most customers still prefer to finalize their purchases or make important decisions offline. This underscores the necessity of integrating online and offline strategies to boost overall conversion rates and enhance the customer experience. Most of the companies studied lack the capability for end-to-end analytics; therefore, they cannot accurately measure the effectiveness of their marketing campaigns at all stages of the buyer journey. This makes it difficult to understand which channels and tactics deliver the most impact.